Nekotorye osobennosti reaktsii serdechno-sosudistoj sistemy na fizicheskuyu nagruzku u invalidov-amputantov, zanimayushchikhsya sportom - Kobzev, Yu. A.; Khramov, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The aim of this paper was the studying of the reaction of the cardiovascular system on the standard physical load and the physical serviceability of the team of physically handicapped amputees (volleyball in a chair). There were 18 men aged 19-44 years with amputations of the lower extremities of a various level (9 - with one or both extremities at the level of the top third part of hip, 9 with the absence of one or both shins) were surveyed. The experience of volleyball in a chair was 1-9 years. The period from the moment amputation was 8-24 years. 7 athletes before reception of the trauma were actively engaged in various kinds of sports. The speed of the restoration of cardiac rate and arterial pressure after physical load does not depend on the level of amputation. It is determined by physical serviceability of the probationer. The normotonic type of the reaction at the satisfactory time of the rally remains the reliable criterion of the high functional preparedness of probationers. Its formation during occupations of physical culture and sports displays the optimization of cardiovascular system functioning in physically handicapped.